Nivel de competencia gramatical en inglés de los estudiantes de la carrera de Idiomas, 2017 - Fernández Salvatierra, Marisol Melany (2019)
The present research had as a final objective to determine “The level of grammatical competence in English students of Language school, 2017 ", which is processed in quantitative approach and descriptive design, for which were applied the techniques of research of written standardized test._x000D_ The sample was made up of 138 persons who were students of 1st, 2nd and 3rd year of_x000D_ Languages career in English, 2017 of the National University of Trujillo._x000D_ The results that were obtained, show us a high level of grammatical competence in English language in the majority of students from 1st to 3rd year of Language school of National University of Trujillo.